Assembleia Fitofossilífera de Lycopodiopsis cf. Derbyi da formação Corumbataí, bacia do Paraná, São Paulo, Brasil - Carvalho, Thaís Silvana de (Universidade Federal de São Carlos, 2019)
The most abundant lycophytes from the fossil record of the Corumbataí Formation, Paraná Basin, are the Lycopodiopsis derbyi Renault, 1890, found in Guadalupian strata. Lycopodiopsis cf. derbyi present a wide occurrence in the rocks of the Passa Dois Group, which makes this taxón of great importance in the floristic scenery of the southwestern Gondwana, constituting part of the coastal vegetation of extensive flooded plains in the territory that today is the State of São Paulo and Southern Brazil. Brazil. The present study was carried out in the city of Rio Claro, State of São Paulo, in an outcrop, where an unprecedented and expressive phytopossiliferous assembly was preserved. The specimens found were attributed to Lycopodiopsis cf. Renault derbyi, preserved as compressão-impressions, and counter-molds and in a North-South direction. They were distributed over a large area, with massive concentration of specimens, including overlap, indicating the possible taphonomic conditions that led to the assembly. The fragmentation of the specimens occurred in the collection process, since in situ they were whole. There is a dichotomy in some stem fragments and throughout the assembly, there was different preservation among the specimens, with the preservation of three distinct levels of cauline decortication (characteristic of the group of Lepidodendrales). This register possibly comprises a non-selective parautochthonous monospecific assembly as it is a massive assembly. The morphological analyzes led to corroborate the decortication characteristic of the group, since in the same specimen there was the preservation of two cortical levels. Also, a branch over one meter long was recorded. It was the first record of a large group-to-group ratio, which although they were arboreal, were believed not to develop at high heights. This assembly presents the first record of mass mortality of Lycopodiopsis derbyi, described for the Corumbataí Formation. From the analysis and further interpretation of the data, it was possible to conclude that despite the massive concentration of individuals, the event that caused their deposition was not of great energy, as it preserved so many anatomical characters, and also allowed the preservation of a fish. articulated together with the branches. Also, dispersive energy spectroscopy (EDS) and stereomicroscope and scanning electron microscope (MEV) images indicated the occurrence of salts, which suggests a deposition paleoenvironment of brackish water-soaked areas.
Phytopossiliferous assembly of Lycopodiopsis cf. Derbyi of Corumbataí formation, Paraná basin, São Paulo, Brazil
Keywords: Neopermiano; Gondwana; Grupo passa dois; Permiano; Lycopodiopsida; CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL; CIENCIAS BIOLOGICAS::BOTANICA::PALEOBOTANICA; CIENCIAS BIOLOGICAS::BOTANICA; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL::ANATOMIA VEGETAL